E-Government platform for the lusophone Africa's national assemblies - Bento, Pedro M. Sousa (2013)
This document and the developed work lie on the perception that the World is always changing. Internet has taken a major role in one's daily routine and is the vehicle to spread the most quantity of information, that mankind as ever witnessed. Regions of the World such as Europe and the Americas, have great ease in exchanging information between the citizens and their governments, but this reality does not re ect in every continent, and Africa is one that still presents insu ciencies regarding this matter. To ful l some of the needs of African countries, in which regards E-Government services communication, the United Nations developed the African I-Parliaments Project, which developed the Bungeni Parliamentary System. This system aims to help automatize the legislative process of African Parliaments. By analysing the system and developing tools, the work described in this document tries to get the Bungeni Parliamentary System to be implemented in the Lusophone Africa, therefore allowing ease of legislation access and creation, through the Internet, helping in the building of government to citizens transparency.